Development of indigenous manufacturing infrastructure in Nigeria: a case: study of the pace-setter organic fertilizer plant (2008)
This paper presents the overview of the research and development (R&D) of the Pace-setter organic fertilizer plant. The plant, is owned, funded and managed by the Oyo State Government through the Ministry of Environment. The plant is located at the Bodija Market in Ibadan North Local Government area. The 10 tons/day capacity plant, designed and constructed (using locally sourced materials, was installed and commissioned in the year 1998. About 35 - 50 tons/day of solid waste consisting of Market Refuse (MR) and Abattoir Waste (AW) generated within the market are used as raw materials for the production of organic fertilizer. The plant is semi-mechanised as sorting and turning are done manually while the processing of the compost into finish products is done mechanically. The processing plant consists of six different units: shredding, screening; pulverizing, mixing, pelletising and bagging. Two grades of organic fertilizer (A and B) are produced in the plant. Grade A is fortified, grade B is unfortified. Both grades are produced in either powder or pellet form. The estimated man-power and electric-energy requirement of the plant are about 25 persons and 70KW respectively. A 50 kg bag of grade 'A' organic fertilizer is sold for about #700, while the unfortified grade 'B' is sold for about #500 per bag. The plant has proven to be commercially viable in terms of employment and income generation and equally as sustainable solution to the problem of solid waste management.